Departamentos en duplex (Summa+, 1997)
Edificio Viel 218, Bs.As. arq. Esses-Naistat; Edificio Arvela 2842, Bs.As. arq. Mazo-Achábal; Edificio Otega y Gasst 1710, Bs.As. arq. Faena; Edificio Arce, Bs.As. arq. Bodas-Miani-Anger